Comercio electrónico en Colombia: retos normativos para una realidad en constante evolución (2020)
This work has as its end and purpose, to analyze the law of electronic commerce, in relation to the efficiency of the law, its applicability and regulatory progress, establishing the basic aspects of the law and advances generated in the Colombian legal system, equally In this way, the ideal procedure will be identified that allows the consumer to react to transactional and even punishable situations and carry out a review of the legal framework, taking into account its development and evolution. The methodology used is of a qualitative nature and of exploratory and descriptive work, by revealing the basic aspects and the way in which law has been transformed into electronic commerce, based on a documentary analysis, from a legal perspective, supported by a survey aimed at demonstrating the consumer's knowledge about how to obtain access to the protection of their rights and access to justice. First, a sweep of the entire subject is carried out, starting from the history and evolution, all the normative and legal development and the state entities in charge of this subject, then a deployment is carried out by the typical behaviors, identification of crimes, in the work of buying and selling products, consumer protection in Colombia and legal responsibility, finally, the mechanisms against possible attacks that both consumers and commercial establishments could suffer are highlighted, and the applicability of the guide as consultation instrument for the user.